Providing Innovative Processes in the Economic Development of the Russian Regions - Olim T. Astanakulov; Natalia V. Kuchkovskaya; Patimat S. Bataeva; Natalia I. Khokhlova; Mauricio Calesci (Space and Culture, India, 2019)
One of the most important demonstrations of the modern economy is the growing importance of innovation. The innovative process, or the process of technological change is a complex concept encompassing the improvement of products, production processes, raw materials as well as management methods. Therefore, the central  aim of the research is to analyse the innovative processes that contribute to the development of the state economy. To accomplish the objectives, we carried out the calculations to examine the relations between the cost indicators, modelling, correlation and regression analyses. The particularities of business processes in innovative activities of organisations leads to uneven distribution, specific cost structure in the crisis and the traditional situation of an insignificant share of innovation in the financing process. The study presents mathematic model of innovation activities of an enterprise, based on economic indicators of current operations. The object of the research are industrial enterprises. Since an important segment of business processes in innovation is small innovative companies, our task is to develop a methodology for forecasting the number that would be suitable for them. From the findings of our research, we concluded that the models that had been previously developed were more effective at the micro level. Based on the analysis of the distribution of costs between technological, marketing, organisational innovations by types of innovation and economic activities by building an adequate set of statistical models, we have identified the following particularities: the basic internal (directly dependent) and external (indirectly affecting) factors that affect the selected performance characteristics.